2015
DOI: 10.1108/ccm-07-2014-0086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cultural positions on FDI’s entry mode

Abstract: Purpose – The purpose of this paper is to study the influence of cultural positions on the choice of entry mode in foreign direct investment (FDI) – joint ventures vs wholly owned subsidiaries. The paper focusses on the impact of cultural positions along four cultural dimensions, as well as on the interactions between these positions and FDI’s contextual variables (i.e. linguistic differences). Design/methodology/approach – A fuzzy set q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…This result lends support to the argument that highly individualistic countries are more willing to bear the risk of foreign investments, regardless of legal origin. Benefits increase the more different societies are in tackling specific problems, because differences in the individualism/collectivism dimension bring uniquely different problem and conflict-solving skills to the table (López-Duarte et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result lends support to the argument that highly individualistic countries are more willing to bear the risk of foreign investments, regardless of legal origin. Benefits increase the more different societies are in tackling specific problems, because differences in the individualism/collectivism dimension bring uniquely different problem and conflict-solving skills to the table (López-Duarte et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, countries with high cultural distance (or dissimilar countries) are less likely to invest in each other (Beugelsdijk and Frijns, 2010; Grosse and Trevino, 1996). On the other hand, foreign investments in wholly owned subsidiaries are more likely to happen between countries with high cultural distance (López-Duarte et al , 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Several recent studies, although focusing on different target regions, have emphasized the importance of general business conditions for attracting foreign investment in the hotel industry (Barrowclough, 2007;Chen, Dimou, 2005;López-Duarte, Vidal-Suárez, González-Díaz, 2015;Salazar, 2005;Yang, Luo, Law, 2014).…”
Section: Distancementioning
confidence: 99%
“…According to Malhorta and Sivakumar (), cultural distance has curvilinear and interaction effects on the level of equity participation. Moreover, it has been established that there is the existence of interaction effects among cultural positions along different dimensions, as well as between cultural positions and FDI's contextual variables (López‐Duarte, Vidal‐Suárez, & González‐Díaz, ). A study by Wei, Xie, and Zhang () found a negative relationship between cultural distance and choice of WOS.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%